Performing history : approaches to history across musicology - November, Nancy (Academic Studies Press, 2020)
"The fifteen essays of Performing History glimpse the diverse ways music historians "do" history, and the diverse ways in which music histories matter. This book's chapters are structured into six key areas: historically informed performance; ethnomusicological perspectives; particular musical works that "tell," "enact," or "perform" war histories; operatic works that works that "tell," "enact," or "perform" power or enlightenment; musical works that deploy the body and a broad range of senses to convey histories; and histories involving popular music and performance. Diverse lines of evidence and manifold methodologies are represented here, ranging from traditional historical archival research to interviewing, performing, and composing. The modes of analyzing music and its associated texts represented here are as various as the kinds of evidence explored, including, for example, reading historical accounts against other contextual backdrops, and reading "between the lines" to access other voices than those provided by mainstream interpretation or traditional musicology"--